The narrative and dramatic construction between the vision of the script and the director: بان جبار خلف (Al-Academy, 2020)
The relationship between the vision of the scenario and the director is represented in the second search for new mechanisms and possibilities that possess the direct effect and synonyms of the vision of the scenario, so he works on investing them in achieving his ideas and visions with more effectiveness and flexibility to achieve creative potentials, without resorting to the installations and expressive structures themselves that have exhausted their meaning, and lost their luster due to Its prevalence and familiarity on the one hand, and its activation on the other hand to achieve modernity at the level of aromas, after the director takes a method or approach that has privacy and exclusivity, and based on the foregoing, getting to know the mechanisms of dealing with the directive vision and seeing the scenario is an urgent necessity that contributes to the exploration of expressive capabilities at the level of Narrative and dramatic construction in film art.